PENGARUH CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK KECANTIKAN MS GLOW (STUDI KASUS PADA KONSUMEN WANITA DI DESA TEGALHARJO KABUPATEN BANYUWANGI) - Fegahyanti, Dita; Widodo, Joko; Mustika Ani, Hety (Universitas Nusantara PGRI Kediri, 2022)
This study aims to determine the significant influence of the brand image of MS Glow beauty products on purchasing decisions of female consumers in Tegalharjo Village, Banyuwangi Regency. This research was conducted by correlational quantitative method using simple linear analysis method. The data collection method used in this study is a closed questionnaire method with a Likert scale, interviews and literature study. The results showed significant results, namely the brand image variable can influence purchasing decisions by 70.6%, the remaining 29.4% is influenced by other variables not examined in this study.